Continuity and change in all-age schools, 1948-88 - Evans, Hyacinth L. (Institute of Social and Economic Research, UWI, 1996)
Information for this review of developments in Jamaican all-age schools from 1948 to 1988 was obtained mainly from primary sources such as reports of committees, annual reports of the Ministry of Education, the Census of Jamaica, reports of conferences, supplemented by recollections of teachers, principals, and education officers. It is concluded that the all-age school, which was established in the 19th century for the labouring classes, continues to be patronized mainly by this group and frustrates the aspirations of many
Keywords: All-age schools